PRODUCTION OF BOLAINA (Guazuma crinita Mart) PLYWOOD GLUED WITH UREA-FORMALDEHYDE AND PHENOL-FORMALDEHYDE RESINS - Castro, Milciades Leonidas Miguel; Iwakiri, Setsuo; Trianoski, Rosilani; Mora, Hector Henrique Gonzales (Floresta, 2022)
The objective of this research is to evaluate the quality of plywood produced with wood veneers of bolaina (Guazuma crinita Mart.) and lupuna (Ceiba pentandra [L] Gaertn) as reference species. Panels were produced with the following dimensions: 600 mm x 600 mm x 10 mm (five layers), according to a factorial arrangement of (3x2), with three veneer compositions (bolaina, lupuna, and bolaina/lupuna) and two formulations for each adhesive (A: 45.9% and B: 35.8% of total solids) for urea-formaldehyde; (B: 40% and C: 34.3%) for phenol-formaldehyde, a gramage of 380 g/m2 in double glue line, a specific pressure of 0.6 MPa, a temperature of 115 ºC, and 8 minutes of pressing time for urea-formaldehyde; and 1.0 MPa, 130 ºC and 6 minutes of pressing time for phenol-formaldehyde. The formulation effect does not have a significant influence on the physical and mechanical properties of the panels, which is an important aspect from an economic viewpoint. However, the interaction with the species used in the composition of the plywood did have a significant influence on said properties. The shear strength and the percentage of failure of the wood used for the panels meet the minimum requirements established in Standard EN 314-2 (1993) for panels for internal and external use, and it is therefore concluded that Guazuma crinita Mart. meets the technical feasibility criteria for producing plywood for internal as well as external use.